2011
DOI: 10.5941/myco.2011.39.3.206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seed-borne Mycoflora from Sorghum and Foxtail Millet Seeds on Germination and Disease Transmission

Abstract: The seed-borne mycoflora of sorghum and foxtail millet collected from different growing areas in South Korea were isolated and taxonomically identified using dry inspection, standard blotter and the agar plate method. We investigated the in vitro and in vivo germination rates of disinfected and non-disinfected seeds of sorghum and foxtail millet using sterilized and unsterilized soil. The percent recovery of seed-borne mycoflora from the seed components of sorghum and foxtail millet seeds was determined and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In general, other studies report the susceptibility of these grasses to attacks of fungi from genre Bipolaris, Exserohilum and Curvularia, which cause spots in leaves and stalks, besides drying the leaves and killing the seedlings (Macedo and Barreto, 2007;Martinez et al, 2010;Kleczewski et al, 2012;Braz et al, 2013;Kumar et al, 2013), however, some authors realized that this result may vary in accordance with the genotype used (Braz et al, 2013). Yago et al (2011) observed that there was an increase in the seedling death percentage for sorghum and foxtail millet seeds inoculated with Curvularia lunata and increase in the severity index for infected seedlings 10 days after the inoculation.…”
Section: Pathogenicitymentioning
confidence: 53%
See 1 more Smart Citation
“…In general, other studies report the susceptibility of these grasses to attacks of fungi from genre Bipolaris, Exserohilum and Curvularia, which cause spots in leaves and stalks, besides drying the leaves and killing the seedlings (Macedo and Barreto, 2007;Martinez et al, 2010;Kleczewski et al, 2012;Braz et al, 2013;Kumar et al, 2013), however, some authors realized that this result may vary in accordance with the genotype used (Braz et al, 2013). Yago et al (2011) observed that there was an increase in the seedling death percentage for sorghum and foxtail millet seeds inoculated with Curvularia lunata and increase in the severity index for infected seedlings 10 days after the inoculation.…”
Section: Pathogenicitymentioning
confidence: 53%
“…The presence of fungi on vegetal tissues was also reported by Yago et al, (2011) who studied sorghum and foxtail millet seeds and identified Curvularia sp. on the seeds' endosperm and Alternaria and Fusarium on the seeds' endosperm and embryo.…”
Section: Transportation Of Fungi Associated With Forage Plant Seedsmentioning
confidence: 85%
“…Appearance of Alternaria leaf spots on coriander in naturally infected, non-inoculated pots in greenhouse trials and seed transmission experiments proved its seed transmission. Similarly, A. alternata has been reported as seed-borne and seed-transmitted in maize, sorghum, foxtail millet and many other hosts (Basak and Lee, 2002;Fakhrunnisa and Ghaffar, 2006;Yago et al 2011;Meena et al 2013;Perelló and Larrán, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Seeds with high initial vigour, foliage growth and good germination provide more biomass and also provides edge to weed competition in their natural growth conditions (Maity et al, 2016). One of the main impediments towards the availability of good quality seeds is seed borne pathogens (Naqvi et al, 2013;Kononenko et al, 2015), which account for annual economic loss of more than US $130 million in Afro-Asian countries (Yago et al, 2011). They reduce seed viability by associating with the seed either externally or internally and may cause seed abortion, seed rot, seed necrosis and reduction or elimination of germination capacity as well as seedling damage.…”
Section: Introductionmentioning
confidence: 99%